Against Environmental Ethics - Jøker Bjerre, Henrik (Filozofski vestnik, 2023)
The kinds of specifically ethical questions we can meaningfully ask about the environment are rapidly becoming fewer as the climate emergency intensifies. The article argues that there is something fundamentally inadequate about the traditional conceptions of ethics regarding the climate crisis because they all tend to presuppose that we can somehow get it right. The problem is that we got it wrong and must start dealing with the consequences.